Variability and reliability of punching impact kinetics in untrained participants and experienced boxers - Lenetsky, S.; Brughelli, M.; Nates, R. J.; Cross, M. R.; Lormier, A. V. (The Journal of Strength and Conditioning Research, 2018)
Striking impact kinetics are central to performance in combat sports. Despite a multitude of assessment, few in the literature have explored the variability and reliability of punching force assessment. Consequently, this study assessed the variability and reliability of measured punching impact kinetics in untrained and experienced boxers using a recently developed and validated method of striking dynamometry. Intrasession (both cohorts) and intersession (untrained only) measures of impulse, peak, and mean force were determined across 4 punch types (jabs, crosses, lead, and rear hand hooks) using coefficient of variation (CV), intraclass correlation coefficients (ICCs), and typical error of measurement (TEM). Moderate (ICC <0.67 or CV >10%) to small (ICC >0.67 and CV <10%) variability was found for intrasession results of both groups, the majority having small variability. Intersession findings of the untrained cohort had a similar spread of variability, but with the majority exhibiting moderate variability. All variables except for mean force of the cross in the experienced boxer cohort were found to exhibit a "moderated" magnitude of reliability determined by standardized TEM scores (TEM = 0.60-1.19) during intrasession testing. All variables had moderate reliability during intersession. This method was found to have acceptable variability and reliability when monitoring punching impact kinetics.